El juego y la motricidad gruesa en los niños de 4 a 5 años de la escuela de educación básica particular Betel ubicado en la ciudad de loja, período 2019-2020 - Benitez Poma, Briggette Silvana (2021)
The present investigation had as a general objective to analyze the importance of games in the gross motor skills of children aged 4 to 5 years. This study has a descriptive scope; The object of study was to know how the game develops skills and abilities in gross motor skills, the methods used were: descriptive, analytical, synthetic, qualitative, quantitative, inductive and deductive. The population consisted of 2 teachers and 19 children from 4 to 5 years old. The instruments used were: a survey applied to the teachers; and the Nelson Ortiz Scale. The results allow to establish that: 100% of the children present a medium level in the gross motor area. In order to improve their gross motor skills either in the physical, psychosocial and emotional aspects, a proposal called "I am happy playing" was developed based on a guide with recreational activities as a tool that was provided to the teacher to be executed in order to to help and reinforce gross motor skills. Concluding thus that when applying the scale it was possible to show that all the children have a medium level in the gross motor area, preventing them from the correct movement, balance and strength of the gross parts of the body, thus observing a notorious motor clumsiness.